Il prelievo delle cellule staminali mesenchimali dal tessuto adiposo - Battaglini, G.; Guadalascara, F.; Monteleone, G. (Lo Scalpello - Journal, 2019)
MESENCHYMAL CELLS SAMPLING FROM ADIPOSE TISSUEThe treatment of chondral and tendinous lesions with staminal cells is today widely used and well accepted by thescientific community. In our first attempts, we did not pay much attention to the phase of sampling mesenchymal cellsfrom the adipose tissue. Local complications and aesthetic gripes led us to a constant evolution in the samplingtechnique. Today, we have achieved a good sampling technique with a very low rate of local complications andvirtually invisible scars.